EFFECT OF THE REFLEXOTHERAPY ON THE QUALITY OF LIFE IN PATIENTS WITH CHRONIC TENSION-TYPE HEADACHE - L. N. BELIMOVA; V. A. BALYAZIN (Кубанский научный медицинский вестник, 2018)
Aim. To estimate the effect of reflexotherapy and standard pharmacological therapy on quality of life in patients with chronic tension-type headache (CTTH).Materials and methods. 95 patients (16 men and 79 women) with CTTH have been taken as the object of research. All patients were divided into two clinical groups. Patients of group 1 received amitriptyline 35-70 mg/day and tolperisone 450 mg/day. Patients of group 2 were assigned to 2-4 courses of injecting reflexotherapy according to the suggested methodology. The intensity of headache was assessed on the basis of scores on the Visual Analogous Scale (VAS). The quality of life was evaluated in all the patients with the aid of the SF-36 survey.Results. In both clinical groups there was decrease in quality of life in all scales except physical function (PF). All patients positively evaluated the results of the treatment. The intensity of pain reduced to 1,7±0,78 points (p<0,05) in the 1st group and 1,65±0,79 (p<0,05) in the 2nd group. As a result of the treatment, quality of life improved significantly in all scales except social function (SF). This index didn't statistically differ in both groups (p>0,05).Conclusion. CTTH significantly affect physical and mental components of patients’ health. The results obtained from the study showed the potential use of injecting reflexotherapy as treatment for CTTH.